Serum small extracellular vesicle‐derived LINC00853 as a novel diagnostic marker for early hepatocellular carcinoma - Soon Sun Kim; Geum Ok Baek; Hye Ri Ahn; Suna Sung; Chul Won Seo; Hyo Jung Cho; Suk Woo Nam; Jae Youn Cheong; Jung Woo Eun (Molecular Oncology, 2020)
This study aimed to identify novel long noncoding RNA (lncRNA) biomarkers for hepatocellular carcinoma (HCC) using publicly available tissue genomic datasets and validate their diagnostic utility for early‐stage HCC. Differentially expressed lncRNAs between 371 HCC and 50 nontumor tissues were obtained from The Cancer Genome Atlas liver hepatocellular carcinoma (TCGA_LIHC) project. Subsequently, the expression of the serum‐ and extracellular vesicle (EV)‐derived lncRNA was assessed in 10 patients with HCC and 10 healthy controls using RT–qPCR. The candidate lncRNAs were validated in 90 HCC and 92 non‐HCC (29 healthy control, 28 chronic hepatitis, 35 liver cirrhosis) patients. The sensitivity, specificity, and area under the receiver operating characteristic curve (AUC) were calculated for the candidate lncRNAs and the current HCC biomarker, alpha‐fetoprotein (AFP). SFTA1P, HOTTIP, HAGLROS, LINC01419, HAGLR, CRNDE, and LINC00853 were markedly upregulated in HCC in TCGA_LIHC dataset. Among them, LINC00853 has not been reported in relation to HCC before. In patients with HCC, only expression of small EV‐derived LINC00853 (EV‐LINC00853) was increased. EV‐LINC00853 showed excellent discriminatory ability in the diagnosis of all‐stage HCC (AUC = 0.934, 95% confidence interval = 0.887–0.966). Moreover, using a 14‐fold increase and 20 ng·mL−1 as cutoffs for EV‐LINC00853 expression and AFP level, respectively, EV‐LINC00853 was found to have a sensitivity of 93.75% and specificity of 89.77%, while AFP showed only 9.38% sensitivity and 72.73% specificity for the diagnosis of early‐stage HCC (mUICC stage I). EV‐LINC00853 had a positivity of 97% and 67% in AFP‐negative and AFP‐positive early HCC, respectively. Serum EV‐derived LINC00853 may be a novel potential diagnostic biomarker for early HCC, especially for AFP‐negative HCC.